2023
DOI: 10.3389/fpsyg.2023.1073647
|View full text |Cite
|
Sign up to set email alerts
|

Effects of online mindfulness-based interventions on the mental health of university students: A systematic review and meta-analysis

Abstract: ObjectivesMental health problems among university students are a cause of widespread concern. Mindfulness-based interventions (MBIs) delivered online have considerable potential to help university students manage mental health challenges. However, there is no consensus regarding the efficacy of online MBIs. This meta-analysis aims to determine whether MBIs are feasible and effective for improving university students’ mental health.MethodsRandomised controlled trials (RCTs) in Web of Science, PubMed, Cochrane L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 53 publications
0
14
1
Order By: Relevance
“… First-author, year No. of participants Intervention Comparison Mental disorders Outcomes Effect metrics Overall Rating Gong et al., 2023 ( Gong et al., 2023 ) 447/461 MBCT Inactive (waitlist) Depression, anxiety, stress Depression, anxiety, stress SMD Moderate Oliveira Silva et al., 2023 ( Oliveira Silva et al., 2023 ) 609/574 Simulation; compared conventional educational strategies with simulation Conventional educational interventions Stress, anxiety Stress, anxiety SMD High Chandler et al., 2022 ( Chandler et al., 2022 ) 6558/6356 CBT-I-based interventions Waitlist or treatment as usual (passive) Alternative intervention (active) Sleep disturbance, anxiety, depression Sleep, anxiety, depression SMD Low Du et al., 2022 ( Du et al., 2022 ) 369/332 Taijiquan intervention Regular physical activity group Depression, anxiety Depression, anxiety SMD Low Huber et al., 2022 ( Huber et al., 2022 ) 320/312 Active intervention Active animal control Active other control No-treatment control Acute anxiety, acute self-perceived stress, negative affect Acute anxiety, acute self-perceived stress, negative affect SMD High Lin et al., 2022 ( Lin et al., 2022 ) 712/714 Qigong exercise Original sports exercise practices, relaxation training or maintaining the original lifestyle without any intervention Depression, anxiety, mood Depression, ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… First-author, year No. of participants Intervention Comparison Mental disorders Outcomes Effect metrics Overall Rating Gong et al., 2023 ( Gong et al., 2023 ) 447/461 MBCT Inactive (waitlist) Depression, anxiety, stress Depression, anxiety, stress SMD Moderate Oliveira Silva et al., 2023 ( Oliveira Silva et al., 2023 ) 609/574 Simulation; compared conventional educational strategies with simulation Conventional educational interventions Stress, anxiety Stress, anxiety SMD High Chandler et al., 2022 ( Chandler et al., 2022 ) 6558/6356 CBT-I-based interventions Waitlist or treatment as usual (passive) Alternative intervention (active) Sleep disturbance, anxiety, depression Sleep, anxiety, depression SMD Low Du et al., 2022 ( Du et al., 2022 ) 369/332 Taijiquan intervention Regular physical activity group Depression, anxiety Depression, anxiety SMD Low Huber et al., 2022 ( Huber et al., 2022 ) 320/312 Active intervention Active animal control Active other control No-treatment control Acute anxiety, acute self-perceived stress, negative affect Acute anxiety, acute self-perceived stress, negative affect SMD High Lin et al., 2022 ( Lin et al., 2022 ) 712/714 Qigong exercise Original sports exercise practices, relaxation training or maintaining the original lifestyle without any intervention Depression, anxiety, mood Depression, ...…”
Section: Resultsmentioning
confidence: 99%
“…Of the 19 included systematic reviews, 26 % ( n = 5) ( Bolinski et al., 2020 ; Huber et al., 2022 ; Lin et al., 2022 ; Luo, Zhang, Liu, Ma & Jennings, 2022 ; Oliveira Silva et al., 2023 ) studies were rated as “high”, 26 % ( n = 5) ( Gong et al., 2023 ) ( Yang, Guo, Cheng & Zhang, 2022 ) ( Harrer et al., 2019 ; Huntley et al., 2019 ; Ma, Zhang & Cui, 2019 ) as “moderate”, 37 % ( n = 7) ( Chandler et al., 2022 ; Du et al., 2022 ) ( Chen et al., 2021 ; Lo et al., 2018 ; Luan et al., 2022 ) ( Huang, Nigatu, Smail-Crevier, Zhang & Wang, 2018 ; Song, Liu, Huang, Wu & Tao, 2021 ) as “low” and 11 % ( n = 2) ( Regehr, Glancy & Pitts, 2013 ; Zhang, Li & Wang, 2022 ) as “critically low” quality with the AMSTAR2 scoring system. Supplementary Table 1 presented the details of the quality of each included study evaluated using the AMSTAR2 tool.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 44 Advanced technological infrastructure, such as broad and high-speed internet access, provides a solid foundation for the development and adoption of digital mindfulness applications. 24 The success of this implementation is also influenced by the high awareness and understanding of mental health among developed societies, which creates significant demand for mental health innovation, including through digital approaches. 45 High levels of digital literacy in developed countries indicate that their people are better able to access and use mental health technology, strengthening the adoption of digital mindfulness.…”
Section: Discussionmentioning
confidence: 99%
“…Previous systematic review showed that the effects of digital mindfulness can significantly reduce stress and depression. 24 However, there is no review that describes various types of digital mindfulness to improve mental health in students. Various information about digital mindfulness is needed to provide an overview for health workers in improving their mental health.…”
Section: Introductionmentioning
confidence: 99%